Condom Use in the Context of Main and Casual Partner Concurrency: Individual and Relationship Predictors in a Sample of Heterosexual African American Men. (May 2017) - Hicks, Megan R.; Kogan, Steven M.; Cho, Junhan; Oshri, Assaf
Researchers have identified engagement in sexual concurrency, particularly when condom use is inconsistent, as a risk factor for HIV and other sexually transmitted infections. This risk is particularly salient in rural communities in which dense interconnection of sexual networks can promote the spread of sexually transmitted infections. The authors investigated individual and relationship factors that predict inconsistent condom use in the context of main and casual partner sexual concurrency among 176 rural African American men. The individual psychosocial factors investigated included impulsivity and anger/hostility. Relationship variables included fidelity expectations, criticism from partners, and relationship control in both main and casual relationships. No individual risk factors were associated with main partner inconsistent condom use; however, impulsivity and anger/hostility positively predicted inconsistent condom use with a casual partner. Relationship control in the main partnership predicted inconsistent condom use with the main partner. Criticism from the main partner positively predicted inconsistent condom use with a casual partner. Finally, expectations for a casual partner's fidelity positively predicted inconsistent condom use with that partner. These findings underscore the importance of considering the influence of one sexual partnership on behavior in another and of taking this complexity into account in the development of preventive interventions.